Molecular Mechanisms of Biofilm Formation in Helicobacter pylori - Kartika Afrida Fauzia; Wiwin Is Effendi; Ricky Indra Alfaray; Hoda M. Malaty; Yoshio Yamaoka; Muhammad Mifthussurur (Antibiotics)
Background: Biofilm formation in Helicobacter pylori (H. pylori) helps bacteria survive antibiotic exposure and supports bacterial colonization and persistence in the stomach. Most of the published articles have focused on one aspect of the biofilm. Therefore, we conducted the current study to better understand the mechanism of biofilm formation, how the biofilm contributes to antibiotic resistance, and how the biofilm modifies the medication delivery mechanism. Methods: We conducted a literature review analysis of the published articles on the Helicobacter pylori biofilm between 1998 and 2024 from the PubMed database to retrieve eligible articles. After applying the inclusion and exclusion criteria, two hundred and seventy-three articles were eligible for our study. Results: The results showed that biofilm formation starts as adhesion and progresses through micro-colonies, maturation, and dispersion in a planktonic form. Moreover, specific genes modulate each phase of biofilm formation. Few studies have shown that mechanisms, such as quorum sensing and diffusible signal factors, enhance coordination among bacteria when switching from biofilm to planktonic states. Different protein expressions were also observed between planktonic and biofilm strains, and the biofilm architecture was supported by exopolysaccharides, extracellular DNA, and outer membrane vesicles. Conclusions: This infrastructure is responsible for the increased survival of bacteria, especially in harsh environments or in the presence of antibiotics. Therefore, understanding the biofilm formation for H. pylori is crucial. This study illustrates biofilm formation in H. pylori to help improve the treatment of H. pylori infection.